2020
DOI: 10.1002/jocb.480
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Age, Gender, and School Setting on Children’s Creative Thinking Skills

Abstract: The current study aimed to investigate whether age, gender, and testing environment may have an effect on children’s creativity in a real‐life setting. Participants included 111 children aged from seven to eleven years. They were given one verbal (Guilford’s Alternative Uses Task) and one figural (Test for Creative Thinking–Drawing Production) creative thinking task either in their everyday classroom or in their school “art room.” On average, in the verbal task, girls tended to outperform boys in fluency and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…As such, there was an age ceiling that limits the generalizability of these findings. This is important because there is some evidence indicating that DT increases with age (Fusi et al, 2021; Shah & Gustafsson, 2021), at least up to middle-age (until about 40 years-old; Massimiliano, 2015; Reese et al, 2001). The creativity literature overall would benefit from extending data collection to older samples to gain a better understanding of life span creativity…”
Section: Discussionmentioning
confidence: 99%
“…As such, there was an age ceiling that limits the generalizability of these findings. This is important because there is some evidence indicating that DT increases with age (Fusi et al, 2021; Shah & Gustafsson, 2021), at least up to middle-age (until about 40 years-old; Massimiliano, 2015; Reese et al, 2001). The creativity literature overall would benefit from extending data collection to older samples to gain a better understanding of life span creativity…”
Section: Discussionmentioning
confidence: 99%
“…Sharp (2001) argues that the development of creativity in childhood does not occur in a steady, linear manner but the ability to be original in relation to a particular domain only appears in adolescence. Similarly, Shah and Gustafsson (2020) find that divergent thinking (DT)-the generation of multiple responses or ideas to a given stimulus-improves with age. The nature of the relationship between age and creativity therefore remains a topic of debate in the literature (Alves-Oliveira, Arriaga, Xavier, Hoffman, & Paiva, 2022).…”
Section: Individual Correlates Of Creativitymentioning
confidence: 96%
“…A substantial strand of the creativity literature therefore examines the individual differences that may account for diverse outcomes in creativity. In terms of the effects of gender on creativity, the results are mixed: males register relatively better scores for creativity in some studies (Scott, Leritz, & Mumford, 2004) but worse scores in others (Castillo‐Vergara, Barrios Galleguillos, Jofré Cuello, Alvarez‐Marin, & Acuña‐Opazo, 2018; Kuhn & Holling, 2009; Shah & Gustafsson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, given the fact that divergent thinking (DT) is the foundation of creativity and imagination, Shah and Gustafsson (2021) conducted a study on British primary school students’ creative thinking using verbal and figural creative thinking tasks, noting that students’ DT, on average, increased with age (grade level) for verbal originality and verbal elaboration. However, a meta-analysis of 16 papers from 1970 to 2018 exploring the effect of age on DT indicated that there may not be a linear relationship between age and DT (Fusi et al, 2021); namely, one’s divergent thinking does not necessarily increase or decrease by age.…”
Section: Literature Reviewmentioning
confidence: 99%